Secure mobile AES encryptor (SMAE) - Satia, Anbalagan (2016)
The purpose of this project is to identify a way to develop a mobile web application for the encryption and decryption of files using the 256 –bit Advanced Encryption Standard (AES) encryption algorithm. This is to ensure the data or files being shared between users are secure from and breach. When a user wants to send a file which contains confidential and important information, the user can protect the data inside the file by encrypting the data using the application developed using their mobile phones and send it to the person they intended to send the data. The reason the AES encryption algorithm selected is because it is considered as one of the most secure encryption algorithm. This can be proved where the National Security Agency (NSA) in the United States to encrypt confidential data and information. This application will focus more on the user of the Android operating systems based mobile phone users. Besides that, the application is developed as a web based application to ensure the application can be accessed using both mobile application as well as web browser. On the other hand, the proper testing of the application is done to ensure that there is a proper user satisfaction level of the users of the application. This is done using the User Acceptance Test to evaluate the user experience while using the application as the objective of the application development is also to improve the interface as well as the functionality of the application compared to the similarly available applications in the Google Play Store.